The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1063/1.4926511
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and numerical modeling of the effect of voltage parameters on the characteristics of low-pressure argon dielectric barrier discharges

Abstract: In this paper, we have presented the experimental and modeling results of the effect of voltage parameters on the characteristics of the low-pressure Ar dielectric barrier discharge. The frequency and amplitude range was set at 5–19 kHz and 255–370 V, respectively. Our investigations showed that the voltage parameters such as amplitude and frequency have large impact on the discharge behavior. Increase in applied voltage amplitude leads to an increase in discharge current. It is also shown that with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Based on pure air gap discharge simulation [28], the cathode secondary electron emission coefficient is set to 0.004. According to description of secondary electron from material surface reference DBD simulation [11], secondary electron emission of PI surface is set to 0.5; the average energy of secondary electrons ɛ = 2.5 eV [29]. The flux boundary for species k considers a flux contribution due to migration and an inward or outward mass flux determined by surface reactions.…”
Section: Wall Boundary Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on pure air gap discharge simulation [28], the cathode secondary electron emission coefficient is set to 0.004. According to description of secondary electron from material surface reference DBD simulation [11], secondary electron emission of PI surface is set to 0.5; the average energy of secondary electrons ɛ = 2.5 eV [29]. The flux boundary for species k considers a flux contribution due to migration and an inward or outward mass flux determined by surface reactions.…”
Section: Wall Boundary Conditionmentioning
confidence: 99%
“…With the leap of computer computing and storage capacity and development of numerical simulation methods, it is possible to simulate micro‐parameters, such as electric field and charge distribution, in discharge process. At present, the simulation of discharge mostly focuses on air gap discharge [9, 10] between needle‐plate electrodes and dielectric barrier discharge (DBD) between plate electrodes [11, 12]. Compared with surface discharge, the effect of solid insulation on the discharge process need not be considered in the air gap discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…The literature [17] considered 12 kinds of particles and 31 kinds of chemical reactions to establish a surface discharge model in N 2 /O 2 environment and obtained the distribution rule of surface charge. Although some progress has been made in these studies, the current simulation of gas discharge is mostly concentrated on the DBD between the plate electrodes [18,19] or the surface discharge under the needle-plate electrode, while the simulation of partial discharge is still in the exploratory stage. Therefore, it is necessary to carry out simulation research on partial discharge of insulation defects of the epoxy interface under the excitation of highfrequency sinusoidal voltage.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of computer technology and storage capacity and the establishment of numerical simulation methodologies, it is now possible to measure micro‐parameters in the discharge process, such as the electric field and charge distribution. Air gap discharge between needle‐plate electrodes and dielectric barrier discharge (DBD) between plate electrodes are the two most common discharge simulations at the moment [6, 7]. Edmiston et al.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of computer technology and storage capacity and the establishment of numerical simulation methodologies, it is now possible to measure micro-parameters in the discharge process, such as the electric field and charge distribution. Air gap discharge between needle-plate electrodes and dielectric barrier discharge (DBD) between plate electrodes are the two most common discharge simulations at the moment [6,7]. Edmiston et al [8] showed a correspondence between pressure, pulse amplitude, microwave frequency, and the delay time of destructive discharge on the surface within a large range of experimental parameters by using high-power microwave (HPM) surface-flashover experiments.…”
Section: Introductionmentioning
confidence: 99%